1996
DOI: 10.1093/ajcp/106.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Transfusion-Associated Cytomegalovirus Infection:Practice Parameter

Abstract: Cytomegalovirus (CM V) infection has been a recognized complication of transfusions for nearly three decades.' More recently, it has been shown that transfusion-related CMV infections present considerable problems for the immunocompromised patient. 23 The potential morbidity and mortality due to transfusion-related CMV infections in this group of patients are very high. Policies and procedures to prevent the unintentional transmission of this virus are critical. Current strategies consist of screening blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Consequently, with the appropriate quality control measures in place, our results will likely be applicable to other institutions and will allow this approach to be used for other populations at high risk for transfusion-associated infections. 10,12 …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, with the appropriate quality control measures in place, our results will likely be applicable to other institutions and will allow this approach to be used for other populations at high risk for transfusion-associated infections. 10,12 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, primary infection or reactivation of the latent virus in congenitally infected neonates or immunosuppressed patients, in particular tissue or organ transplant recipients and HIV-infected patients, can lead to serious clinical manifestation. The transmission of HCMV via blood products containing cells should be avoided at all costs by means of appropriate precautions (see 4.2) in the following HCMV-negative patients and in the case of intrauterine transfusions [7,14,23,25]: -HCMV-seronegative pregnant women, -premature infants with a birth weight of less than 1,200 g born to HCMV-seronegative mothers, -HCMV-seronegative potential recipients of allogenic stem cell transplants, -HCMV-seronegative recipients of allogenic stem cell transplants from HCMV-seronegative donors, -HCMV-seronegative recipients of organ transplants from seronegative donors, -HCMV-seronegative AIDS patients. The prevention of HCMV infection from blood products containing cells is also often recommended for the following patient groups: -HCMV-seronegative patients with Hodgkin's disease, -HCMV-seronegative patients receiving immunosuppressive therapy, especially if they have a tendency towards opportunistic infections, -HCMV-seronegative recipients of autologous stem cell transplants, -HCMV-seronegative patients with congenital or acquired deficiencies of cellular immunity.…”
Section: Severity and Course Of The Diseasementioning
confidence: 99%
“…Patients who receive polychemotherapy and/or irradiation treatment for an underlying malignant disease often experience a transient disturbance of cellular immunity but which does not usually progress to HCMV disease as a result of a primary or secondary infection [14].…”
mentioning
confidence: 99%
“…1 Transfused WBCs have been associated with febrile transfusion reactions, alloimmunization and subsequent platelet refractoriness, 2 transmission of cytomegalovirus (CMV) and other infections, 3 up-regulation or reactivation of latent host viruses, 4 and immune suppression of the recipient. 5,6 For many years it has been observed that red blood cell components from allogeneic donors contain WBCs capable of survival and expansion.…”
Section: Introductionmentioning
confidence: 99%